What are new opportunities for clinical practice the VERIFY study opens and which values for native diabetes patients? Joint conclusion on the advisory board results. November 6, 2019 - Marina V. Shestakova; Mikhail B. Antsiferov; Alexander S. Ametov; Gagik R. Galstyan; Tatiana Y. Demidova; Alexey V. Zilov; Tatiana N. Markova; Nina A. Petunina; Natalya A. Chernikova; Minara S. Shamkhalova (Сахарный диабет)
According to key diabetic studies, the early use of metformin glucose lowering therapy is associated with a reduced risk of developing micro- and, in the long term, 10-year follow-up, macrovascular complications and cardiovascular mortality. Short-term studies results on combined glucose lowering therapy with metformin suggests that combination therapy can have several advantages on the one side from the effectiveness of glycemic control and on another side from positive effect on the development of complications of type 2 diabetes. The question of the start time of combined hypoglycemic therapy remains open. According to the results of recent large-scale studies, real world evidence data, careful glycemic control during the first year from the moment of diagnosis of type 2 diabetes is crucial for further management of the disease and slow the progression of complications. However, due to the fact that the clinical benefits of early combination therapy were not demonstrated in randomized clinical trials, this approach, despite the theoretical background, was not recommended for widespread use in international guidelines for the treatment diabetes patients. Russian algorithms on the treatment diabetes patients recommend combined glucose lowering therapy at the start of treatment at a HbA1c level of 1% higher than the target. A 5-year VERIFY study results were demonstrated long-term sustained glycemic control in combination with vildagliptin + metformin prescribed for native diabetes patients with relatively low HbA1c values, as well as the advantages of this approach in comparison with the standard strategy for phased intensification of monotherapy. The results of the VERIFY study provided a wealth of information to discuss early treatment intensification, the clinical benefits of this approach and a possible review of the treatment strategy for native diabetes patients.